Primate models of interference control. (February 2015) - Watanabe, Kei; Funahashi, Shintaro
Highlights: Interference control is an ability to protect ongoing cognitive processing from distractors. Dual-task paradigms provide important information to elucidate the flexible allocation of cognitive resource for interference control. Animal studies using the dual task help to understand the neural mechanisms of interference control. Abstract: Interference control is the ability to protect ongoing cognitive processing from internal or environmental distraction. For an individual to achieve interference control appropriately, either a control mechanism to coordinate multiple processing streams, such as the central executive in working memory, a mechanism to flexibly allocate the cognitive resource with a limited capacity for performing each task, or both, are needed. Through the use of dual-task paradigms, animal studies have provided important information to elucidate the neural mechanisms of the central executive and the flexible allocation of cognitive resource. These animal studies should help to promote our understanding of the neural mechanisms of interference control.